EVALUASI PROGRAM PEMBINAAN PUSLATDA CABANG OLAHRAGA ANGGAR SUMATERA SELATAN DALAM MENGHADAPI PON JAWA BARAT - Herri Yusfi; Destri Ani; Destri Ana (Universitas Sriwijaya, 2019)
This study aims to 1) evaluate the KONI Regional Training Program of the South Sumatra Province Fencing Sports Program, 2) evaluate the KONI management, IKASI management, athletes, coaches and assistant coaches, facilities and infrastructure, and government support for the training center of KONI Province of South Sumatra , 3) evaluating the implementation of coaches and athletes selection, athlete coaching, training programs, pre-work evaluation and coordination of Puslatda South Sumatra programs, and 4) evaluating the success of the South Sumatra Puslatda Anggar program. This study is a program evaluation study using the CIPP method using a quantitative qualitative approach. The population of this study was Puslatda Anggar KONI South Sumatra. Data collection techniques are observation, in-depth interviews, documentation, and data triangulation. This study produces 1) Context less, 2) Sufficient Input 3) Good Process 4) Enough. This study concludes that 1) Development Program that is not clear from PELTI in improving athlete performance, 2) Input of the fencing area training program program is still lacking in the process of selecting athletes, coaches, assistant coaches and minimal funding from the government, 3) Training program process which runs well, according to the schedule and performance of the trainers, 4) Product Program Guidance training for the Fencing area has not been able to show the results that are very good at the West Java PON level